PENGARUH PEMBERIAN BOKASHI LAMTORO DAN FREKUENSI NPK TERHADAP PERTUMBUHAN DAN HASIL OKRA PADA TANAH GAMBUT - Pradana, Gusti Fitrah; Darussalam, Darussalam; Palupi, Tantri (Agros Journal of Agriculture Science, 2023)
This study aims to determaine the interaction and dose of bokashi lamtoro and the frequency of NPP on the grwoth and yield of okra and peat soil. This study used a factorial Randomized Block Design (RBD) consisting of 2 factors. The first factor is bokashi lamtoro which consists of 3 levels, b1 = 10 tons/ha equivalent to 1,5 kg/per plot, b2 = 15 tons/ha equivalent to 2 kg/per plot, b3 = 20 tons/ha equivalent to 3 kg/per plot, the second factor is the frequency of NPP application, f1 = application twice per plant, f2 = application three times per plant,  with a dose of 600 kg/ha equivalent to 12 g/per plant. Treatmant of 10 ton/ha bokashi lamtoro and three times NPP gave the highest interaction results at 3 WAP plant height and 15 ton/ha bokashi lamtoro and twice NPP gave the highest average fruit weight per fruit and fruit weight per plant on okra on peat soil.  Keywords: Bokashi Lamtoro, NPP Frequency, Pet soil INTISARIPenelitian ini bertujuan untuk mendapatkan interaksi dan dosis bokashi lamtoro dan frekuensi NPK terhadap pertumbuhan dan hasil okra pada tanah gambut. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) yang terdiri dari 2 faktor. Faktor pertama adalah bokashi lamtoro yang terdiri dari 3 taraf, b1 = 10 ton/ha setara ddengan 1,5 kg/per bedengan, b2 = 15 ton/ha setara dengan 2 kg/per bedengan, b3 = 20 to/ha setara dengan 3 kg/per bedengan, faktor kedua adalah pemberian frekuensi NPK, f1 = pemberian dua kali per tanaman, f2 = pemberian tiga kali per tanaman, dengan dosis 600 kg/ha setara dengan 12 g/per tanaman. Perlakuan 10 ton/ha bokashi lamtoro dan pemberian tiga kali NPK memberikan hasil interaksi tertinggi pada tinggi tanaman 3 MST dan 15 ton/ha bokashi lamtoro dan pemberian NPK dua kali memberikan rerata berat buah perbuah dan berat buah per tanaman tertinggi pada okra di tanah gambut. Kata Kunci: Bokashi Lamtoro, Frekuensi NPK, Tanah Gambut